Fast and effective chromatographic separation of polymersomes from proteins by multimodal chromatography - Mertz, Michael; Golombek, Florian; Boye, Susanne; Moreno, Silvia; Castiglione, Kathrin (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2021)
Artificial vesicles made of block copolymers, so-called polymersomes, represent a versatile chassis for the creation of functionalized nanocompartments with a wide range of biotechnological applications. The specific application depends on the biomolecules – usually proteins – that are positioned in the interior, in the membrane or on the surface of the vesicles. However, not all added proteins are integrated into the vesicles during the usual manufacturing processes of polymersomes. Excess proteins must therefore be removed. The separation techniques currently used for this, however, are associated with decisive disadvantages, such as damaged vesicles, long process times, or small sample volumes that can be processed. To overcome these drawbacks, we investigated the applicability of Capto™ Core 700 resin for polymersome purification. Polymersomes were not damaged or otherwise affected by passage through the column verified by hollow fiber flow field flow fractionation technique. Using three proteins with divergent physico-chemical properties as examples, it was demonstrated that different types of unentrapped proteins were efficiently removed from polymersome dispersions. The dynamic binding capacities in the presence of polymersomes varied between 9.5 and 16.5 mg per mL resin for the proteins applied. The technique can be used for small and large sample volumes alike. In addition, it can be used without special laboratory equipment. This adds a new and easy-to-use purification method for polymer vesicles to the repertoire that will also facilitate the large-scale production of functionalized polymersomes.
CRIS-Team Scopus Importer:2021-01-08
Keywords: Multimodal chromatography; Negative purification; Polymer vesicle; Polymersome; Protein separation